2018
DOI: 10.1080/07420528.2018.1513943
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan fasting on feelings, dietary intake, rating of perceived exertion and repeated high intensity short-term maximal performance

Abstract: AR: After Ramadan; AR10: Ten days after Ramadan; AR20: Twenty days after Ramadan; BR: Fifteen days before Ramadan; ER: Last ten days of Ramadan; FI: Fatigue index; FR: First ten days of Ramadan; FS: Feelings scale; HD: Higher distance; PSQI: The Pittsburgh Sleep Quality Index; RPE: Rating of Perceived Exertion Scale; TD: Total distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 38 publications
7
42
4
Order By: Relevance
“…Conversely, one study showed a decrease in protein intake during Ramadan compared to control periods (26). However, the absence of change in protein consumption during Ramadan compared to control periods was reported by six studies (14,(22)(23)(24)(25)28).…”
Section: Protein Intakementioning
confidence: 96%
See 3 more Smart Citations
“…Conversely, one study showed a decrease in protein intake during Ramadan compared to control periods (26). However, the absence of change in protein consumption during Ramadan compared to control periods was reported by six studies (14,(22)(23)(24)(25)28).…”
Section: Protein Intakementioning
confidence: 96%
“…On the other hand, one study reported that the fat intake was lower during Ramadan than control periods (26). However, Trabelsi et al (27) and Boukhris et al (25) showed that the fat intake increased during the month of Ramadan.…”
Section: Fat Intakementioning
confidence: 96%
See 2 more Smart Citations
“…As described by Boukhris et al30 , the RSA testing consisted of six repetitions of a 30 s maximal shuttle sprint over 5 m, 10 m, m and 20 m alternatively…”
mentioning
confidence: 99%